We have to find y such that sin y = cos 3y.

We know that sin(y) = cos(pi/2-y),so we can convert the given equation to:

sin(y) = cos(pi/2-y) = cos(3y)

We now equate pi/2 - y and 3y

pi/2 - y = 3y

=> pi/2 = 3y + y

=>...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to find y such that sin y = cos 3y.

We know that sin(y) = cos(pi/2-y),so we can convert the given equation to:

sin(y) = cos(pi/2-y) = cos(3y)

We now equate pi/2 - y and 3y

pi/2 - y = 3y

=> pi/2 = 3y + y

=> 4y = pi/2

=> y = pi/8

**Therefore y = pi/8 + 2*n*pi**